The Influence of Self-Efficacy, Social Support, Coping Stress and Demographic Factors on Academic Burnout in Final Year Students at UIN Syarif Hidayatullah Jakarta - Sulthon, Mohamad; Baraja, Abdullah (Lafadz Jaya Publisher, 2024)
This study aims to find the effect of self-efficacy, social support, coping stress, and demographic factors on academic burnout in final year students of UIN Syarif Hidayatullah Jakarta. This study aims to examine the effect of each independent variable (self-efficacy, social support, coping stress, and demographic factors) on the dependent variable (academic burnout). The sample consisted of 219 final year students of UIN Syarif Hidayatullah Jakarta, which were taken using non- probability sampling techniques. The data collection instrument used the Maslach Burnout Inventory Student Survey measuring instrument developed by Schaufeli & Salanova (2007) Student Coping Instrument developed by Lazarus & Folkman (1984), the General Self Efficacy Scale (GSES) Scale developed by Sherer (1982), and Multidimensional Scale of Perceived Social Support (MSPSS) developed by Zimet et.al. (1988). The study used confirmatory factor analysis (CFA) to test the validity of the measuring instrument construct and to test the research hypothesis using multiple regression analysis techniques. The results of the major hypothesis test of this study are that there is a significant influence on the effect of self-efficacy, social support, coping stress, and demographic factors on academic burnout. Meanwhile, the results of the minor hypothesis test of this study are that there is a significant effect of variable self-efficacy, family support and special person support on academic burnout in final year students of UIN Syarif Hidayatullah Jakarta. Based on the proportion of all variants, the influence of all Independent Variables is 45% while the other 55% is influenced by other variables outside of this study.